2010
DOI: 10.1158/1541-7786.mcr-10-0181
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 Protects Adenocarcinoma Cells from UV-Induced Apoptosis by Akt and p21-Dependent Pathways of Survival

Abstract: Transcriptional activation of p53 target genes, due to DNA damage, causes either apoptosis or survival by cell cycle arrest and DNA repair. However, the regulators of the choice between cell death and survival signaling have not been completely elucidated. Here, we report that human adenocarcinoma cells (MCF-7) survive UV-induced DNA damage by heat shock protein 27 (Hsp27)-assisted Akt/p21 phosphorylation/translocation. Protein levels of the p53 target genes, such as p21, Bcl-2, p38MAPK, and Akt, showed a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…2, A and B), whereas Hsp27 showed a very slight increase from basal level and remained at the same level. These results are consistent with our previous report that wtp53 undergoes Hsp27-assisted proteasomal degradation in UV-induced DNA-damaged MCF-7 cells (40). Although wtp53 and mutp53 were indistinguishable by Western blotting because the antibody recognizes both, mutp53 is found to be very stable, unlike wtp53.…”
Section: Inhibition Of Hsf-1 Depletion Of Hsp27 and Accumulation Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…2, A and B), whereas Hsp27 showed a very slight increase from basal level and remained at the same level. These results are consistent with our previous report that wtp53 undergoes Hsp27-assisted proteasomal degradation in UV-induced DNA-damaged MCF-7 cells (40). Although wtp53 and mutp53 were indistinguishable by Western blotting because the antibody recognizes both, mutp53 is found to be very stable, unlike wtp53.…”
Section: Inhibition Of Hsf-1 Depletion Of Hsp27 and Accumulation Ofsupporting
confidence: 92%
“…Also, HSF-1 homotrimer can bind to HSE in the MDR1 promoter region in competition with NF-B, to repress MDR1 gene expression (29). Hsp27, upon phosphorylation, interacts with p53 to enhance its degradation (40). In MCF-7/adr cells, HSF-1 and Hsp27 are inhibited, and p53 mutation is enforced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of RP101 to HSPB1 had important functional consequences: interaction with Pro-CASP3, AKT1, and CYC1 was inhibited. HSPB1 acts as a switch between apoptosis and survival by modulating AKT1 stability (Kanagasabai et al 2010). Moreover, RP101 sensitized to heat shock and reduced tumor invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance to apoptosis was through the inhibition of caspase 9 and 3 activation, and this effect might be due to the increased expression of HSP27 [33]. Similar to cisplatin, UV is also known to induce the apoptosis in NSCLC cells, while the increased expression of HSP27 directed the chaperoning interaction with Akt and increased the stability of Akt, increased the phosphorylation of p21, and induced the resistance to UV-induced DNA damage and apoptosis in NSCLC cells [34]. Recent studies in MCF10A (human mammary epithelial cells) and HCT116 (human colon carcinoma cells) indicated that HSP27 regulates the stability of p53 and further modulates cellular senescence and apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%